Psychological characteristics of developing excellence in talented female field hockey players - Edwards, P. L.; MacNamara, A.; Saward, C. (Journal of Sports Sciences, 2023)
Psychological Characteristics of Developing Excellence (PCDEs) are a range of psychological factors that play a key role in the realisation of potential. We examined PCDE profiles across a female national talent development field hockey programme in North America. Two-hundred-and-sixty-seven players completed the Psychological Characteristics of Developing Excellence Questionnaire version 2 (PCDEQ-2) prior to the competitive season. One-hundred-and-fourteen players were classified as juniors (under-18) and 153 as seniors (over-18). Eighty-five players were classified as non-selected (not-selected to their age-group national team), and 182 as selected (selected to their age-group national team). A MANOVA showed multivariate differences based on age, selection status and their interaction, within this already homogenous sample, suggesting that sub-groups within this sample vary depending on their overall PCDE profiles. ANOVA showed differences in imagery and active preparation, perfectionist tendencies and clinical indicators between juniors and seniors. Furthermore, differences in imagery and active preparation, and perfectionist tendencies, were observed between selected and non-selected players. Subsequently, four individual cases were identified for further analysis based on their multivariate distance to the average PCDE profile. The use of the PCDEQ-2 at group- and particularly at individual-levels seems an important tool to support athletes as they navigate their development journey.